Internalizing the externalities of overfunding: an agent-based model approach for analyzing the market dynamics on crowdfunding platforms - Jascha-Alexander Koch; Jens Lausen; Moritz Kohlhase (Journal of Business Economics, 2021)
Crowdfunding platforms offer project initiators the opportunity to acquire funds from the Internet crowd and, therefore, have become a valuable alternative to traditional sources of funding. However, some processes on crowdfunding platforms cause undesirable external effects that influence the funding success of projects. In this context, we focus on the phenomenon of project overfunding. Massively overfunded projects have been discussed to overshadow other crowdfunding projects which in turn receive less funding. We propose a funding redistribution mechanism to internalize these overfunding externalities and to improve overall funding results. To evaluate this concept, we develop and deploy an agent-based model (ABM). This ABM is based on a multi-attribute decision-making approach and is suitable to simulate the dynamic funding processes on a crowdfunding platform. Our evaluation provides evidence that possible modifications of the crowdfunding mechanisms bear the chance to optimize funding results and to alleviate existing flaws.
Keywords: C63; D47; D61; D62; G41; 650; Crowdfunding; Overfunding; Internalization of externalities; Pigouvian tax; Agent-based modeling; Market engineering